Pengaruh Kompetensi, Kompensasi, dan Beban Kerja terhadap Kinerja Petugas Pelaksana Program Makan Bergizi Gratis (MBG) di Desa Mliwis, Kecamatan Cepogo, Kabupaten Boyolali - Nunung Astuti; Luki Sri Anggorowati; Hari Purwanto (Lembaga Pengembangan Kinerja Dosen, 2026)
This study examines the effect of competence, compensation, and workload on the performance of implementing staff of the Free Nutritious Meal (Makan Bergizi Gratis/MBG) Program in Mliwis Village, Cepogo District, Boyolali Regency. A quantitative approach combining descriptive and verificative methods was employed. All 42 program staff were selected as respondents through a saturated sampling technique, and data were collected using a Likert-scale questionnaire. Multiple linear regression analysis was carried out with the assistance of IBM SPSS Statistics, preceded by validity, reliability, and classical assumption tests. The partial test (t-test) showed that compensation had a positive and significant effect on staff performance, whereas competence and workload did not show a significant partial effect. Nevertheless, the simultaneous test (F-test) confirmed that competence, compensation, and workload jointly and significantly influenced staff performance, with an adjusted R square value of 0.754, meaning that the three variables explained 75.4 percent of the variance in performance. These findings suggest that strengthening the compensation system deserves priority attention in efforts to improve the performance of village-level MBG program staff, without disregarding the long-term importance of competence development and proportional workload management.